Identificación de la fauna insectil en el cultivo del arroz oriza sativa en la zona de Arenillas - Ávila Cruz, Javier A. (2005)
The identification of the fauna entomológica is a work of much head-ponsabilidad and dedication, since works like this they are of a lot of help for those producing of rice in the area of Sands; that which is good them to establish technical parameters of possible control of the plagues but significant and of more economic importance for cul-tivo and which are the beneficent insects that exist in the sector. The out-lined objectives were: 1. to identify the plagues of more impor-tancia in the cultivation; 2. to determine the beneficent insects that you in-cuentran regulating the plagues of the cultivation; 3. to establish the classification taxonómica of the specimens gathered in the field. For colec-tar the specimens one carries out traveled by the established cultivations of rice, in the parish the Cuca of the county of The Gold; in those that you muestrearon sembrios that presented deterioration in the foliage and pa-nícula for the presence of attacks of plagues, the same ones that you place-rum in cases or glass flasks to be transferred the laboratory and examined being. All the objective fulfilled jurisdictions in their cabalidad, you ends up identifying and to recog-nize each one of the insects plagues that you/they cause a very harm-ful damage and which are the insects predatores that it controls them.